Elevated Peripheral Visfatin Levels in Narcoleptic Patients - Dahmen, Norbert (Public Library of Science, 2008)
OBJECTIVE: Narcolepsy is a severe sleep disorder that is characterized by excessive daytime sleepiness, cataplexies and a tendency towards obesity. Recent discoveries indicate that the major pathophysiology is a loss of hypocretin (orexin) producing neurons due to immunologically mediated degeneration. Visfatin is a recently described proinflammatory adipokine. It is identical to the immune modulating pre-B-cell colony enhancing factor (PBEF). Our study examines the hypothesis that visfatin levels are altered in narcoleptic patients. METHODS: For the analysis, a total of n = 54 patients (n = 18 males and n = 36 females) with the diagnosis of narcolepsy according to DSM-IV and the International Classification of Sleep Disorders were examined (BMI mean 30.3±5.5, age mean 52.5±16.1 years). As a control group 39 unrelated (n = 12 males and n = 27 females) healthy volunteers with no sleep disorder according to DSM-IV were included (BMI mean 28.5±4.6, age mean 51.1±13.6 years). Peripheral visfatin levels were measured using a commercial enzyme immunoassay kit with a measurement range from 0.1–1000 ng/ml. Narcolepsy symptoms, severity and frequency of symptoms as well as the total duration of various aspects of the symptomatology were assessed by unstructured and structured clinical interviews in including the Stanford Center for Narcolepsy Sleep Inventory. RESULTS: Circulating visfatin was found to be significantly increased in HLA DR2 positive narcoleptic patients compared to controls. CONCLUSION: Taken together, our results add to the evidence of disturbed immunological regulation in patients with narcolepsy.